An Analysis of Insiders' Use of Prepaid Variable Forward Transactions - JAGOLINZER, ALAN D.; MATSUNAGA, STEVEN R.; YEUNG, P. ERIC (Journal of Accounting Research, 2007)
ABSTRACT This study examines firm performance surrounding insiders' prepaid variable forward (PVF) transactions to infer insiders' information when they enter these off‐market contracts. PVFs allow insiders to hedge downside risk, share performance gains, and obtain immediate large‐sum cash payments for investment or consumption. On average, PVF transactions cover 30% of a sample insider's firm‐specific wealth ($22 million), which is substantially larger than a typical open‐market sale. PVFs systematically follow strong firm performance and precede degraded stock and earnings performance. PVFs also precede periods of negative abnormal returns relative to potential alternative investments. The documented association between PVFs and performance declines does not appear to result from the market's response to transaction disclosure, participant self‐selection, or general price reversals. Thus, evidence suggests that insiders use PVFs to diversify firm‐specific holdings in anticipation of performance declines.